Comparison of Condition of Male Pencak Silat Athletes Suriname and Male Pencak Silat West Sumatera - Florence Wangsabesari Jamin; Japhet Ndayisenga; Juanda Putra (International Martial Arts and Culture Journal, 2025)
Purpose. This study aims to compare the physical condition of male pencak silat athletes from West Sumatra and Suriname through nine physical tests (endurance, agility, speed, strength, explosive power, balance, and flexibility). Methods. Descriptive analysis shows that the average physical condition test carried out for speed, agility, strength, flexibility, balance and endurance of athletes from West Sumatra is higher in all components. Result. However, the independent t test showed no statistically significant difference (p > 0.05) in all variables, which means the physical condition of both groups is relatively equal. Conclussions. Research with a larger sample is needed to confirm this finding. The pencak silat culture present in Suriname is also the root of the martial arts sport in Indonesia so it reflects a fairly similar coaching system, recommendations for further research on the pencak silat technique owned by athletes from both countries.